Another new species of Phyllodytes (Anura: Hylidae) from the Atlantic Forest of northeastern Brazil - Orrico, Victor G. D.; Dias, Iuri R.; Marciano-Jr., Euvaldo (Zootaxa, 2018)
A new species of the genus Phyllodytes is described from the State of Bahia, in the Atlantic Rain Forest of Northeastern Brazil. Phyllodytes praeceptor sp. nov. can be differentiated from other species of Phyllodytes by its medium size (SVL 20.7–25.8 mm in males); odontoids moderately developed; vocal sac externally visible; eyes large and prominent; dorsum homogenously cream, except for a few scattered spots and blotches; venter areolate with two parallel, paramedial lines of larger tubercles; few tubercles in the ventral surface of thighs, the largest being the medial one; a large tubercle on the skin around the tibio-tarsal articulation; nuptial pad rounded and moderately expanded.